PHYSIOLOGICAL SELECTIVITY OF INSECTICIDES TO EGGS AND LARVAE OF PREDATOR Chrysoperla externa (HAGEN) (NEUROPTERA: CHRYSOPIDAE) - Torres Soares, Andrea de Fátima; Carvalho, Geraldo Andrade (Coffee Science - ISSN 1984-3909, 2018)
Given the importance of green lacewings as agents of biological pest control, the present study aimed to evaluate the toxicity of insecticides used on coffee crops on the eggs and larvae of Chrysoperla externa. The insecticides tested were (g or mL a.i./L) chlorpyrifos (2.25), cartap hydrochloride (1.66), pyriproxyfen (0.33), profenofos/lufenuron (1.33/0.13), fenpropathrin (0.40), triazophos/deltamethrin (0.70/0.02) and zetacypermethrin (0.05). The insecticides, when applied directly on the eggs, caused no adverse effects on the duration of the embryonic period. After the application of triazophos/deltamethrin, pyriproxyfen, profenofos/lufenuron and zetacypermethrin, a reduction in egg viability was induced. The insecticides triazophos/ deltamethrin, chlorpyrifos, and profenofos/lufenuron reduced the survival of newly hatched first instar larvae from treated eggs. The first instar larvae that were treated directly were sensitive to the effects of the products used, with the effect of triazophos and chlorpyrifos/deltamethrin being high. The survival of the second instar larvae was reduced by zetacypermethrin, fenpropathrin, profenofos/lufenuron, and cartap hydrochloride. The products chlorpyrifos and triazophos/deltamethrin also did not allow second instar larvae survival. For treated third instar larvae, chlorpyrifos and triazophos/deltamethrin allowed survival of only 20.0 and 57.5%. Eggs and larvae of C. externa showed sensitiveness to insecticides chlorpyrifos and triazophos, being needed more studies in semi-field and field conditions for the confirmation or not of the toxicity aiming the conservation of this predator specie on the coffee agroecosystem.